Review of Problem Tooling Breakdown Fixes at the Op10 Part Panel Anniversary, RR W/House Inn, RR L/R (RH) at Pt. Summit Adyawinsa Indonesia - Tiara Wijaya, Elika; Herwanto, Dene; Rabbani Sumitra, Naufal (Jurnal Serambi Engineering, 2026)
Anniversary damage in the stamping process is a critical problem that can affect product quality and hinder smooth production in the automotive industry. This study aims to identify the main cause of damage to the OP10 Anniversary of the RR W/House Inn RR L/R (RH) at PT. Adyawinsa Indonesia Summit and formulate the right improvement steps to reduce the frequency of breakdowns. The research uses a case study approach through direct observation, structured interviews with Maintenance Tooling personnel, as well as analysis of OEE data and damage history for the period June–December 2024. The data were analyzed using the Root Cause Analysis method (Fishbone Diagram and 5 Why) as well as technical evaluation on the insert dies component. The results showed that scratch defects  in parts were caused by damage to the blank holder insert in the form of pin holes and peeling hardchrome layers, which was exacerbated by less effective preventive maintenance and technical inspections that were only visual. This condition caused 39 breakdown events with a total downtime of 41 hours. Repair recommendations are carried out through insert redesign, precision machining, hardening process, re-hard chrome, and improvement of inspection flow and tooling monitoring. In conclusion, improving the quality of inserts and strengthening the preventive maintenance system has been proven to be able to reduce the potential for repeated damage and increase the reliability of the stamping process.